Outcomes of infants born at borderline viability (23–25 weeks gestation) who received cardiopulmonary resuscitation at birth. (9th September 2018) - Goel, Dimple; D'cruz, Daphne; Jani, Pranav
Abstract : Aim: The practice of providing advanced resuscitative measures to infants born at borderline viability (23–25 +6 weeks gestation) varies among clinicians due to perception of futility. The aim of our study was to compare mortality and major morbidities in infants born at borderline viability who did not receive cardiopulmonary resuscitation (CPR) in the delivery room (No DR‐CPR) as compared to those who did (DR‐CPR). Methods: A retrospective analysis of prospectively collected data of infants born between 23 and 25 +6 weeks gestation who were resuscitated at birth at the study centre or admitted to neonatal intensive care unit from peripheral hospitals, over 8 years (2007–2014). The primary outcome was survival, free of disability at 2 years corrected age and secondary outcomes were survival at discharge and neonatal morbidities. Results: Of 123 infants in the study cohort, 21 received DR‐CPR. In unadjusted analysis, there was increased mortality rate in the DR‐CPR group which was statistically insignificant (26.5 vs. 42.9%, P = 0.15). After adjustment for potential confounders, there was no significant difference in the mortality rate with odds ratio of 1.10 (confidence interval: 0.34–3.53, P = 0.86). Among infants who received DR‐CPR for >2 min, the mortality rate was significantly higher (25.2 vs. 56.3%, P = 0.01). Survival free of disability was similar in two groups (50.9 vs. 47.6%, P = 0.78). Conclusions: Among infants born at borderline viability, the vast majority of infants did not receive CPR and, if CPR was prolonged for >2 min, mortality was increased. Among survivors of the small DR‐CPR group, early neurodevelopmental outcomes were comparable to the No DR‐CPR group.